The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/bjophthalmol-2014-306308
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and depressive symptoms in an older Australian cohort: longitudinal findings from the Blue Mountains Eye Study

Abstract: VI was associated with subsequently presenting depressive symptoms over 5 years among older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
36
2
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 24 publications
7
36
2
5
Order By: Relevance
“…Consistent with previous findings, VL was associated with increased depression symptoms over time, although no cross‐sectional relationship was observed. Conversely, we showed that HL had a cross‐sectional, but not longitudinal, association with depression.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous findings, VL was associated with increased depression symptoms over time, although no cross‐sectional relationship was observed. Conversely, we showed that HL had a cross‐sectional, but not longitudinal, association with depression.…”
Section: Discussionsupporting
confidence: 89%
“…To date, the majority of sensory loss and mental health literature has focused on VL and depression. Prior research consistently demonstrates that older adults with VL have an increased risk of depression . Possible mechanisms include a reduction in social activities and subsequent social isolation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cross-sectional design precludes elucidation of temporal relationships (eg, between visual function and education, employment, and occupational categories), which is necessary to confirm causality, the findings nevertheless serve to identify the existence of patterns of inequality and delineate new hypotheses for testing in longitudinal research to identify pathways of action. 25 The epidemiologic literature 22,[26][27][28] on visual function in adults has understandably principally addressed the worst end of the spectrum (ie, low vision and blindness), which is known to be associated with belonging to an ethnic minority and having lower socioeconomic status. Longitudinal research on the 1958 British birth cohort by our group 17,24 provided the conceptual basis for the present study that has exploited the greater scale and diversity of UK Biobank, albeit using crosssectional data, to identify and understand current patterns of social inequalities in visual health across the spectrum from normal vision to VI, SVI, and blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature examining social support for adults with visual impairments has shown that social support relates more strongly to SWB in people with visual impairments than other variables measuring visual function (Guerette and Smedema, 2011;Huurre et al, 1999;Papadopoulos, et al, 2014;Pinquart and Pfeiffer, 2013). However, few studies have focused on older adults (e.g., Court et al, 2014;Hong, et al, 2015). Further research is required to examine whether social support mediates and moderates the effect visual difficulties on SWB for oldest-old adults in order to suggest effective interventions.…”
mentioning
confidence: 99%